An adaptive dynamic reference control for power converters in a microgrid - Jayan, Vijesh (2022)
This paper proposes an adaptive dynamic reference control for power converters in a microgrid. Conventionally, two separate controllers are required to control the input current and the dc bus voltage. The proposed adaptive dynamic reference control eliminates the need for an additional controller by utilizing a simple discrete-time model to generate appropriate input current reference for the dc bus voltage regulation. The proposed technique is easy to design and guarantees a dynamic convergence of the dc bus voltage to its nominal reference even during nonidealities in the system, such as model parameter uncertainties, sensor imperfections, and unmodelled dynamics. A simple design procedure of the control parameters for the desired converter response is also provided based on a theoretical analysis. Unlike traditional linear controllers, the control parameter design of the proposed model is independent of the converters operating point. Finally, the performance of the proposed technique is validated experimentally by using a finite control set model predictive control of a typical grid-connected application and is compared with both conventional dynamic reference control and traditional linear controller.